Improved mechanical properties of antimicrobial poly(N-[3-(dimethylaminopropyl)] methacrylamide) hydrogels prepared by free radical polymerization in the presence of cetyltrimethylammonium bromide as a lyotropic liquid crystal template - Sabah, Cansu Kozbekci; Yalçın, Bestenur; Şimşek, Ceyda; Gürsel, Yeşim H.; Erbil, Candan (Royal Society of Chemistry (RSC), 2022)
In this study, the effect of liquid crystal templates on improving the mechanical and antibacterial properties of poly(N-[3-(dimethylaminopropyl)] methacrylamide) hydrogels was investigated.
Keywords: Acrylamides; Free Radicals; Cetrimonium; Hydrogels; Anti-Bacterial Agents; Liquid Crystals; Polymerization; Surface-Active Agents; Anti-Infective Agents; Escherichia coli